Towards energy-efficient high-throughput photonic NoCs for 2.5D integrated systems: a case for AWGRs - Werner, Sebastian; Fotouhi, Pouya; Proietti, Roberto; Xiao, Xian; Yoo, S. J. Ben (Proceedings of the Twelfth IEEE/ACM International Symposium on Networks-on-Chip, 2018)
Silicon Photonics (SiPs) can overcome the energy and bandwidth limitations of electrical interconnects in networks-on-chip (NoCs) and enable efficient global all-to-all connectivity-the ideal from a performance perspective. Unfortunately, state-of-the-art SiP switching fabrics impose power overheads for thermo-optical control of microring resonators (MRs), excessive crosstalk, or challenging physical layout. The Arrayed Waveguide Grating Router (AWGR) is a SiP device that provides layout-efficient and scalable all-to-all connectivity through wavelength-routing on a passive and compact platform. Recent technological advances now enable AWGR integration with significantly reduced footprint (<1mm2), crosstalk (<-38dB), and loss (<2dB), making AWGRs emerge as a major enabler for energy-efficient all-to-all connectivity in NoCs. This paper, for the first time, populates the design space of AWGR-based NoC topologies and compares AWGRs to state-of-the-art SiP fabrics and aggressive electrical baselines. Our results make a compelling case for AWGRs in interposer-based systems with processor disintegration, which have high bandwidth demands, large on-chip distances, and less stringent area constraints. AWGR-based NoCs can offer an average of 1.67x power savings, 1.23x speed-up, and 1.5x lower energy-delay-product (EDP) on PARSEC3.0/SPLASH-2x workloads compared to electrical baselines, and fewer waveguides, wavelengths, or MRs than alternative SiP crossbar fabrics.